Perspectives of test examiners of the localized speaking assessment framework: a case study in Vietnam - Truong, Thi Nhu Ngoc; Abd Samad, Arshad; Phan, Thi Thanh (Universiti Putra Malaysia Press, 2021)
The present study explores the test examiners' perspectives on the role and qualitative aspects of the current localized speaking assessment framework used in Vietnam. A case study with two experienced test examiner-cum-English lecturers was conducted. Inductive content analysis was used to analyze the qualitative data findings obtained from individual semi-structured interviews. Drawbacks, merits, and standardization issues of the current localized speaking assessment frameworks, i.e., the Vietnamese Standardized Test of English Proficiency (VSTEP), were also discussed, especially in comparison to internationally recognized examinations and frameworks such as the International English Language Testing System (IELTS) and the Certificate in Advanced English (CAE) as well as the Common European Framework of Reference for Languages (CEFR). The study informed both English educators and policymakers to improve localized speaking assessment to suit the local teaching needs while still meeting the requirements of widely accepted international proficiency tests.